Submillimeter galaxy overdensities around physically associated quasar pairs - Herwig, Eileen; Arrigoni Battaia, Fabrizio; Chen, Chian-Chou; Obreja, Aura; Nowotka, Marta; Remus, Rhea-Silvia; Yajima, Hidenobu (Astronomy and astrophysics, 2025)
A commonly employed method to detect protoclusters in the young universe is the search for overdensities of massive star-forming galaxies, such as submillimeter galaxies (SMGs), around high-mass halos, including those hosting quasars. For this work we studied the megaparsec environment surrounding nine physically associated quasar pairs between z = 2.45 and z = 3.82 with JCMT/SCUBA-2 observations at 450 μm and 850 μm covering a field of view of roughly 13.7′ in diameter (or 32 Mpc2 at the median redshift) for each system. We identified a total of 170 SMG candidates and 26 non-SMG and interloper candidates. A comparison of the underlying 850 μm source models recovered with Monte Carlo simulations to the blank field model reveals galaxy overdensities in all fields, with a weighted average overdensity factor of δcumul = 3.4 ± 0.3. From this excess emission at 850 μm, we calculate a star formation rate density of 1700 ± 100 M⊙ yr−1 Mpc−3, consistent with predictions from protocluster simulations and observations. Compared to fields around single quasars, those surrounding quasar pairs have higher excess counts and more centrally peaked star formation, further highlighting the co-evolution of SMGs and quasars. We do not find preferential alignment of the SMGs with the quasar pair direction or their associated Lyα nebulae, indicating that cosmic web filaments on different scales might be traced by the different directions. Overall, this work substantiates the reliability of quasar pairs to detect overdensities of massive galaxies and likely sites of protocluster formation. Future spectroscopic follow-up observations are needed to confirm membership of the SMG candidates with the physically associated quasar pairs and definitively identify the targeted fields as protoclusters.
Gesehen am 17.02.2026
Online veröffentlicht: 31. Oktober 2025